Asymmetric total synthesis of eicosanoid - Mohapatra, Debendra K.; Yellol, G. S. (Arkivoc, 2005)
An asymmetric total synthesis of eicosanoid 4 starting from 2,2- dimethyl-( R)- 1,3- dioxolane-4- carbaldehyde is described. The key steps involved for the synthesis include modified Simmons-Smith cyclopropanation, stereoselective reduction, ring-closing metathesis (RCM) and Nozaki- Hiyama- Kishi coupling reaction.
Keywords: cyclopropanation; eicosanoid; lipoxygenase inhibitors; Ring-closing metathesis; Stereoselective

Chiral 2-C-methylene glycosides and carbohydrate-derived pyrano[2,3-b][1]benzopyrans: synthesis via InCl3 catalyzed stereoselective ferrier rearrangement of 2-C-acetoxymethyl glycal derivatives - Ghosh, R.; Chakraborty, A.; Maiti, D. K.; Puranik, Vedavati G. (Tetrahedron Letters, 2005)
2-C-Acetoxymethyl glycal derivatives react with aliphatic alcohols in the presence of InCl3 (30 mol %) to furnish the corresponding 2-C-methylene glycosides in excellent yields and with exclusive alpha-selectivity except for the methyl 2-C-methylene glycosides, which are formed in similar to 2:1 anomeric ratio in favour of the alpha-anomer. The reaction of 2-C-acetoxyglycals with phenols, however, produces the corresponding chiral carbohydrate-derived pyranobenzopyran derivatives via initial Ferrier rearrangement followed by tandem cyclization in excellent yields and moderate to high stereoselectivities in favour of the corresponding 10a-R-pyrano[2,3-b][1]benzopyran derivatives. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 2-C-methylene glycoside; InCl3; pyranobenzopyran; Stereoselective

Stereoselective synthesis of the C33-C44 fragment of palau'amide - Mohapatra, Debendra K.; Nayak, Sabita (Tetrahedron Letters, 2008)
An efficient stereoselective synthesis of the C33-C44 fragment of palau'amide is described using a Sharpless asymmetric epoxidation, a regioselective nucleophilic ring opening of the epoxide, a Grignard reaction and a Luche stereoselective reduction of a keto compound as the key steps. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Cytotoxic; Luche's stereoselective reduction; palau'amide; Sharpless asymmetric epoxidation; Stereoselective

Protecting group directed stereoselective reduction of an epi-inosose: efficient synthesis of epi-inositol - Patil, Madhuri T.; Krishnaswamy, Shobhana; Sarmah, Manash P.; Shashidhar, Mysore S. (Tetrahedron Letters, 2011)
A facile and high yielding synthesis of epi-inositol via stereoselective reduction of a pentaprotected epi-inosose is reported. Extent of stereoselectivity during the hydride reduction appears to depend on the ability of the substrate to complex with metal ions in the reducing agent. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Polyol; reduction; Stereoselective

Atom-economical and scalable asymmetric synthesis of daridorexant key starting material (S)-2-methylproline via the memory of chirality - Bhatt, Gaurang J.; Kumar, Shubham; Mhaske, Santosh B. (Organic Process Research & Development, 2025)
alpha-Methylproline is a key starting material (KSM) for important drugs, such as Daridorexant, Veliparib, Trofinetide, Enlicitide chloride, and Usnoflast. A practical and scalable asymmetric synthesis of (S)-2-methylproline and its derivatives has been disclosed here using a diketopiperazine intermediate-based strategy that leverages the memory of chirality. Commencing from an inexpensive starting material, l-proline, it proceeds through dimerization and alkylation, followed by hydrolysis under mild conditions, avoiding column chromatography to furnish enantiomerically pure (S)-2-methylproline.HCl, which was also converted to (S)-Boc-2-methylproline and (S)-2-methylproline methyl ester.HCl. In contrast to prior multistep approaches, which rely on expensive chiral auxiliaries and hazardous reagents, this concise three-step route offers operational simplicity, scalability, and superior stereochemical control, making it an attractive method for the synthesis of proline-derived building blocks for peptidomimetics and pharmaceutical applications.
Keywords: alpha-methylproline; atom economy; memoryof chirality; Stereoselective

Bioinspired synthesis of bridged isochromane fused pyrazoles by a silver catalyzed cascade reaction and its application for antibacterial activity - Singh, Bhuvnesh; Tewari, Shreya; Kaur, Manleen; Sharma, Himanshu; Vanka, Kumar; Singh, Neetu; Singh, Ravi P. (JACS Au, 2025)
A stereoselective silver catalyzed one pot vinylogous aldol addition followed by a cascade [4+2] cycloaddition reaction of α-arylidene pyrazolinones to in situ generated isochromenylium ions has been developed, which provides an unprecedented bridged [2.2.2] [3.3.1] pentacyclic [5-6-6-6-6] skeleton consisting of an isochroman, chroman, and a pyrazole unit in one molecule with good to high yields as a single diastereomer. This method offers mild reaction conditions, wide substrate compatibility, excellent scalability and easy derivatization. A DFT study was carried out to clarify the reaction mechanism. It was exciting to observe that the unprecedented bridged isochromans synthesized here have shown excellent selectivity toward Gram-positive and Gram-negative bacteria. We demonstrate that while some structures are broad spectrum antibacterial there are two distinct structures that can be explored for selective activity.
Keywords: Antibacterial; Bridged [2.2.2] [3.3.1]; ROS; Stereoselective; Vinylogous aldol addition; [4+2] cycloaddition